Penilaian Kinerja Pegawai berbasis pelayanan administrasi kepegawaian tanpa kertas dikantor Badan Kepegawaian Daerah Provinsi Sumatera Utara - james sances silaban; Ika Sartika; ayu widowati johannes (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
Bureaucratic reform is one of the efforts made by the government to make a fundamental change in carrying out governance, especially in terms of institutional (organizational), governance (implementation process), and human resources (Government Apparatus). (Rudito, 2016:48) The driving force for bureaucratic reform is the realization of good governance based on services by utilizing information technology in the administration of local governments. Information technology in the administration of government is called electronic government (e-gove). North Sumatra Provincial Government in improving Civil Service Management has implemented Paperless (paperless) with the e-gove system in the administration of personnel administration. The paperless personnel administration service (Paket Keras) has been implemented in the North Sumatra Province Regional Personnel Agency office, including in the performance evaluation based on paperless personnel administration service (Paket Keras). In performance appraisal according to Grote (1996) in the book The Complete Guide To Performance Appraisal says that there are three approaches to performance appraisal, namely (a) Performer-Based Performance Assessment, (b) Behavior-Based Performance Assessment, (c) Results-Based Performance Assessment. The research method used is qualitative research with descriptive methods and inductive approaches. Data collection techniques used through interviews, observations, documentation and data from informants, namely the Head of the Regional Personnel Agency of North Sumatra Province, Secretary, Head of Personnel Information and Data, Formation, Development, and Welfare, and Civil Servants in the scope of the BKD Office in Sumatra Province North. Data reduction data analysis techniques, data presentation, and conclusions. Employee Performance Evaluation based on paperless personnel administration services at the North Sumatra Province BKD office has not been carried out optimally. However, in its implementation there are several obstacles / obstacles including there are still employees who do not understand or master the Paket Keras system, there are still employees who have not changed their mindset, there are still employees who do not understand the development of information technology (IT), application tutorials are still incomplete , the budget is still constrained in completing the work program, and the slow approval of the P-APBD. The advice that I can give is that normatively the regulations issued as a basis for Paket Keras-based performance appraisal need to be strengthened again, for example by issuing circular letters about the time limit of tolerance in data filling and accompanying sanctions for employees who do not implement the policy. Based on human resources there needs to be an increase in the quality of the implementation team which is the main component, besides that users in this case civil servants must always be given deeper socialization in order to master the Paket Keras system. Need to increase the sense of employee awareness related to the needs of each individual to be competent in terms of technology and information (IT), so that employees are not confused by the development of IT such as the Paket Keras.